1961
DOI: 10.1111/j.1478-4408.1961.tb02423.x
|View full text |Cite
|
Sign up to set email alerts
|

The Hydrolysis of Reactive Dyeings

Abstract: Twelve reactive dyes were synthesised containing the same chromophore but different reactive systems and different bridge members. These dyes were applied to mercerised cotton at approximately standard depth and the effects on the dyeings of alkaline and acid hydrolysis were studied. Increasing reactivity of dichloro‐ and trichloro‐pyrimidyl dyes is accompanied by a growing tendency to acid and, more particularly, alkaline hydrolysis. The position at which saponification occurs depends on the nature of the bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1962
1962
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Since this will be affected by buffer-anion affinity, the use of buffers may lead to confusing results. Reference has been made t o anomalous results in acidhydrolysis studies [8] and the probable cause is now shown.…”
Section: Ljkg; Dye 2; 2=2) (Arrows Indicate Typical Experimental Limimentioning
confidence: 94%
“…Since this will be affected by buffer-anion affinity, the use of buffers may lead to confusing results. Reference has been made t o anomalous results in acidhydrolysis studies [8] and the probable cause is now shown.…”
Section: Ljkg; Dye 2; 2=2) (Arrows Indicate Typical Experimental Limimentioning
confidence: 94%
“…It is suggested that, in the case of conventionally dyed cotton, a small amount of dyefibre bond cleavage occurs as a result of the wash-off stages and, particularly, the five-wash fastness tests. It is known that the dye-fibre bond formed using vinylsulfone reactive dyes on cotton is more alkali-sensitive than that derived from monohalotriazine dyes, 8 and this would explain the Remazol RR dyeings having slightly inferior wash fastness to the Procion H-EXL and Cibacron F dyeings. The cotton adjacent picks up the small amount of loose colour that is generated, the stain becoming quite noticeable after five washes; in addition, the colour strength of the dyeing is reduced.…”
Section: Wash Fastness Assessmentmentioning
confidence: 99%
“…[4], [1] In order to improve the exhaustion and consequent fixation of reactive dye on cellulosic and ligno cellulosic substrates, several attempts including introduction of two identical or different reactive groups per chromophore have been reported in the literature with little or marginal improvement in the exhaustion of such dyes into textile substrates. [3] Reactive dye however when applied on proteineous fibres such as wool and silk, more than 90% exhaustion of dye is achieved even without necessitating use of any salt for promotion of exhaustion. [5] Incorporation of amino compounds into cotton and jute prior to dyeing is reported to be prospective with respect to improvement of exhaustion of reactive dye into such modified fibers even in absence of salt.…”
Section: Introductionmentioning
confidence: 99%